The Use of Spices as a Media to Stimulate Childrenâ€™s Critical Thinking Ability while Study From Home Period - Munastiwi, Erni (Journal of Education Technology, 2021)
Critical thinking is an essential aspect of the 21st century. There was an outbreak of pandemic covid-19; some educators had difficulty stimulating critical thinking in early childhood. But for some teachers used spice ingredients at home to promote the critical thinking of children. Therefore, this research aimed to provide critical thinking learning solutions during the covid 19 pandemics. This study used a qualitative descriptive method to describe the use of spices in stimulating essential thinking. The data collection technique using interviews, observations and documentation by involving children aged 5-6 years (n= 15). Data collection, data reduction, data display, and conclusion drawing were analyzed by testing data validity using triangulation techniques.Â  This study showed that using spice media in making turmeric herbs acid, making batik from natural dyes, and making dolls through a scientific approach can stimulate critical thinking ability in children in the study from home. So, can be concluded that using spice media stimulate critical thinking ability in children in the study from home.